Tamaño y densidad de Neaxius vivesi (Thalassinoidea: Axüdae), en Bahía de Los Angeles, Baja California, México - Leija- Tristán, Antonio (Universidad de Costa Rica, 1994)
Digging shrimp Neaxius vivesi (Bouvier 1895) were eollected with harpoon in February, May and August of 1986 in Bahía de Los Angeles, B.C., Mexico (28"53' N; 113"34' W). Burrows were randomly sampled with a Ix l m quadral. 39 speeiemens were captured, 19 in February, 12 in May and 8 in August;. 54% were female, but males were better represented in February and August. Length and weight means were 91.6 mm and 14.6 g. February females and May gmales had the highest means, and maximun individual values were registered for females in February and minimum for females in August. The weight-size, Icorrelation (both sexes) was of r > 0.80 (t > 0.05). A clear alometry was observed .. Density highestcouldreach an average of 9 burrows 1m2. Each burrow had one male and one female, wmch alternated in feeding.